Pre-exposure prophylaxis (PrEP) to HIV in Alas, Brazil: characterization of users, adherence to the protocol and risk behavior for transmissible sexual habits (STIs) - Barbosa, Lucianna Costa de Almeida (2022)
Objective: to characterize the profile of PrEP users, identify the proportion of adherence to the protocol and verify the occurrence of STI diagnosis. Methodology: this is a retrospective study of a quantitative nature, carried out at the Specialized Assistance Service of a northeastern capital. Secondary records taken from the Medication Logistic Control System were used and the collection instrument was a questionnaire based on the PrEP care forms made available by the Ministry of Health. Results: the users' profile points to cis men, brown, aged 30 years or older, of homosexual/gay/lesbian orientation, who perform anal sexual intercourse and have 12 or more years of schooling. During the consultations, a diagnosis of chlamydia and a diagnosis of hepatitis B was made. Regarding adherence to the protocol, it was noticed that there were always users who discontinued the protocol. Conclusion: from this evaluation, we understand some of the strengths and weaknesses of the service offer, aspects that are fundamental for a more complete assistance.